Business Innovation in the Meatball Home Industry: Navigating Market Trends Through Accurate Decision Making - Diah Cahyani; Elok Cahyaning Pratiwi; Anna Kridaningsih; Nidya Rizkawati; Eny Rachmawati; Amelia Silvia; Salwa Aulia Nawa Billah (PT. TAKAZA INNOVATIX LABS, 2025)
This community service initiative focused on supporting home based meatball businesses by enhancing their production processes, packaging methods, and business strategies to adapt to evolving market demands. The program aimed to empower small-scale producers by providing mentorship, introducing technology for inventory management, and promoting sustainable practices. The primary methods used included Participatory Action Research (PAR) and Asset-Based Community Development (ABCD), which involved both producers and consumers in the research process. The results demonstrated significant improvements in operational efficiency, product quality, and market responsiveness. The integration of digital tools and sustainable practices enabled businesses to remain competitive while maintaining product authenticity. This initiative highlights the importance of community collaboration and continuous innovation for small business success.